A phase 2B randomised trial of hyperbaric oxygen therapy for ulcerative colitis patients hospitalised for moderate to severe flares. Issue 6 (3rd August 2020) - Dulai, Parambir S.; Raffals, Laura E.; Hudesman, David; Chiorean, Michael; Cross, Raymond; Ahmed, Tasneem; Winter, Michael; Chang, Shannon; Fudman, David; Sadler, Charlotte; Chiu, Ernest L.; Ross, Frank L.; et al.
Summary: Background: Hyperbaric oxygen has been reported to improve disease activity in hospitalised ulcerative colitis (UC) patients. Aim: To evaluate dosing strategies with hyperbaric oxygen for hospitalised UC patients. Methods: We enrolled UC patients hospitalised for acute flares (Mayo score 6‐12). Initially, all patients received 3 days of hyperbaric oxygen at 2.4 atmospheres (90 minutes with two air breaks) in addition to intravenous steroids. Day 3 responders (reduction of partial Mayo score ≥ 2 points and rectal bleeding score ≥ 1 point) were randomised to receive a total of 5 days vs 3 days of hyperbaric oxygen. Results: We treated 20 patients with hyperbaric oxygen (75% prior biologic failure). Day 3 response was achieved in 55% (n = 11/20), with significant reductions in stool frequency, rectal bleeding and CRP ( P  < 0.01). A more significant reduction in disease activity was observed with 5 days vs 3 days of hyperbaric oxygen ( P  = 0.03). Infliximab or colectomy was required in only three patients (15%) despite a predicted probability of 80% for second‐line therapy. Day 3 hyperbaric oxygen responders were less likely to require re‐hospitalisation or colectomy by 3 months vs non‐responders (0% vs 66%, P  = 0.002). No treatment‐related adverse events were observed. Conclusion: Hyperbaric oxygen appears to be effective for optimising response to intravenous steroids in UC patients hospitalised for acute flares, with low rates of re‐hospitalisation or colectomy at 3 months. An optimal clinical response is achieved with 5 days of hyperbaric oxygen. Larger phase 3 trials are needed to confirm efficacy and obtain labelled approval.